2013
DOI: 10.1242/jeb.079442
|View full text |Cite
|
Sign up to set email alerts
|

Neither male gonadal androgens nor female reproductive costs drive development of sexual size dimorphism in lizards

Abstract: SUMMARYSexual size dimorphism (SSD) is an extensively studied phenomenon in animals, including reptiles, but the proximate mechanism of its development is poorly understood. The most pervasive candidates are: (1) androgen-mediated control of growth, i.e. a positive effect of gonadal androgens (testosterone) on male growth in male-larger species, and a negative effect in female-larger species; and (2) sex-specific differences in energy allocation to growth, e.g. sex with larger reproductive costs should result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 46 publications
(61 reference statements)
4
30
2
Order By: Relevance
“…We expected that these costs could take two forms: (i) since badges act as sex-identifiers [11], males may preferentially court females lacking badges and (ii) since badges result from high levels of plasma testosterone (in males and females; [10]), they may indicate low female fecundity associated with high testosterone in females (e.g. [13]). …”
Section: Introductionmentioning
confidence: 99%
“…We expected that these costs could take two forms: (i) since badges act as sex-identifiers [11], males may preferentially court females lacking badges and (ii) since badges result from high levels of plasma testosterone (in males and females; [10]), they may indicate low female fecundity associated with high testosterone in females (e.g. [13]). …”
Section: Introductionmentioning
confidence: 99%
“…Several species from the genus Paroedura are endangered or even critically endangered (Bora et al., ; Raxworthy et al., ). Nevertheless, the male‐larger Madagascar ground gecko ( Paroedura picta ) has become an emerging laboratory reptile model because of its extremely rapid reproduction for a reptile and relatively easy care (e.g., Kubička & Kratochvíl, ; Kubička, Starostová, & Kratochvíl, , ; Kubička, Schořálková, Červenka, Kratochvíl, ; Schořálková, Kratochvíl, & Kubička, ; Starostová et al., ; Starostová, Angilletta, Kubička, & Kratochvíl, ; Starostová, Kubička, Golinski, & Kratochvíl, ; Starostová, Gvoždík, & Kratochvíl, ). For these reasons we used it for a series of manipulative experiments to investigate the control and correlates of growth, sexual size dimorphism, and body size.…”
Section: Introductionmentioning
confidence: 99%
“…Body size and structural growth is generally believed to be negatively affected by energy limitation and should therefore also be negatively affected by high expenditure due to other energetically demanding processes. However, we discovered that snout‐vent length (SVL) and structural growth in P. picta was unaffected by manipulations of food intake under nutrient conditions allowing continuous reproduction (Kubička & Kratochvíl, ), by energy allocation to reproduction in females (Kubička et al., ; Starostová et al., ), by tail regrowth after tail autotomy (Starostová et al., ), and by castration in males (Kubička, Starostová, & Kratochvíl, ; Starostová et al., ). We suggest that these results can be explained by a simple hierarchical rule of resource allocation followed by the geckos, where the allocation to structural growth and body size have priority over investment in all other energy expenditures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among lizards, the expression of sexually dimorphic morphology and behaviors are associated with elevated levels of androgens present in reproductively active males (Cox et al, 2005;Crews et al, 1978;Golinski et al, 2014;Crews, 1999, 2000;Rhen et al, 2005;Sinervo et al, 2000;Tokarz, 1986;Weiss and Moore, 2004;Woolley et al, 2004, but see Kubička et al, 2013;Starostová et al, 2013;Sanger et al, 2014). Studies have also demonstrated that chemical or pheromonal cues play an important role in social interactions of several species of reptiles, including the eublepharid gecko E. macularius, such as for the identification of conspecifics and distinguishing between the sexes (Brillet, 1993;Cooper and Steele, 1997;Greenberg, 1943;Mason and Gutzke, 1990;Shine et al, 2002;reviewed in Houck, 2009;Martin and Lopez, 2011; but see Hews et al, 2011).…”
Section: Introductionmentioning
confidence: 99%